Molecular chemiluminescent probes with a very long near-infrared emission wavelength for in vivo imaging - Huang, Jingsheng (2022)
Chemiluminescence imaging is imperative for diagnostics and imaging due to its intrinsically high sensitivity. To improve in vivo detection of biomarkers, chemiluminophores that simultaneously possess near-infrared (NIR) emission and modular structures amenable to construction of activatable probes are highly desired; however, these are rare. Herein, we report two chemiluminophores with record long NIR emission (>750 nm) via integration of dicyanomethylene-4H-benzothiopyran or dicyanomethylene-4H-benzoselenopyran with dioxetane unit. Caging of the chemiluminophores with different cleavable moieties produces NIR chemiluminescence probes (NCPs) that only produce signals upon reaction with reactive oxygen species or enzymes, for example, β-galactosidase, with a tissue-penetration depth of up to 2 cm. Thus, this study provides NIR chemiluminescence molecular scaffolds applicable for in vivo turn-on imaging of versatile biomarkers in deep tissues.